Rehabilitation Program for Males Aged 20-30 with Myofascial Pain Syndrome - Sundus Farooq Honi (Wahid Hasyim University, 2026)
Objectives: This study aimed to design and examine the effectiveness of a rehabilitation program combined with shortwave diathermy in reducing pain intensity and improving shoulder range of motion among males aged 20–30 years with upper-back myofascial pain syndrome. Materials and Methods: This study used an experimental one-group repeated-measures design involving pre-test, middle-test, and post-test measurements. The participants were 20 male patients diagnosed with myofascial pain syndrome in the upper-back region at a rehabilitation center in Al-Kut. The rehabilitation program lasted eight weeks and consisted of three progressive phases: pain reduction, flexibility development, and functional strengthening. Shortwave diathermy was applied during the early phase, followed by structured rehabilitation exercises. Pain intensity was measured using the Visual Analog Scale, while shoulder range of motion was assessed through abduction, internal rotation, and external rotation tests. Data were analyzed using SPSS. Results: The findings showed a significant reduction in pain intensity from pre-test to middle-test, particularly in rest pain, pressure pain, and movement-related pain. Further improvement was observed at the post-test, especially in angle pain. Shoulder range of motion also improved significantly across all measured movements, including abduction, internal rotation, and external rotation. Conclusions: The rehabilitation program combined with shortwave diathermy was effective in reducing pain and improving shoulder range of motion in males with myofascial pain syndrome. The integration of deep-heat therapy and progressive rehabilitation exercises may provide a practical approach for restoring functional movement and preventing recurrence.